Analisa Prestasi dengan Perspektif Manajemen: StudiKasus pada PT. Yelooo Integra Datanet Tbk (Yelo) Tahun 2021-2023 - Meilan Sri Despitra; Raifan Wahyu Satria; Zahwa Aulia; Zul Azmi (Yayasan Almanar Pujud, 2025)
This article aims to examine the financial performance of PT. Yelooo Integra Datanet Tbk (YELO) during the 2021–2023 period from a managerial point of view. The analysis centers on the company’s operational aspects, resource management, and profitability. The data were sourced from the annual reports available on the company’s official website:https://passpod.com/id/companyinfo/id– ee66d940-6aea-1e9ac1cc192823746af. The results of the analysis show notable fluctuations in financial performance. In 2021, YELO recorded a net profit of Rp14.66 billion, supported by post-pandemic economic recovery. However, in 2022, although revenue rose sharply to Rp1.56 trillion, net profit declined significantly to Rp345 million. The negative trend continued into 2023 with a net loss of Rp489 million, despite revenue still reaching Rp771 billion. The decline in profitability and solvency ratios over the past three years indicates cost structure pressures, mainly due to rising cost of goods sold and operating expenses. From a managerial perspective, this situation calls for the implementation of efficiency measures and cost restructuring to maintain business sustainability. This study is expected to serve as an evaluative reference on the effectiveness of previously implemented managerial policies and as a foundation for developing future financial strategies.